Architecture Science Field Position in Dew and Fog Harvesting Research: A Bibliometric Analysis - Muhammar Khamdevi; Matius MLT (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2023)
Passive dew and fog harvesting is currently a topic that has begun to develop since the issue of climate change and the water crisis hit the world. Even though this topic is not new, its development has been very intense lately by many researchers from various disciplines. However, this topic has not yet become a major topic of conversation in the world of architecture. Therefore, this bibliometric research was carried out, to see the development of passive fog and dew harvesting research related to architectural science. At the same time to see opportunities for positions that can be filled by researchers and architects to contribute and collaborate on this topic. The database used is from Lens based on eleven keywords related to the topic of dew and fog harvesting. The dataset is then processed in Microsoft 365 Excel and VOSviewer to obtain a scientific mapping which will be interpreted afterwards. The results of this study indicate that there are positions that can be filled and there are still opportunities that can be researched on this topic by architectural scientists, particularly in relation to context, locality, community, sustainability, biomimetics, bioinspiration, and low technology.